Perioperative Bilateral Internal Iliac Artery Balloon Occlusion, In the Setting of Placenta Accreta and Its Variants: The Role of the Interventional Radiologist - Singh, Sristi; Gurung, Padma; Shrestha, Prashant (Nepal Journal of Obstetrics and Gynaecology, 2022)
A case of twenty eight year-old, G3P2 with placenta accreta, oligohydramnios, placenta previa and previous LSCS for placenta previa had undergone bilateral internal iliac artery balloon occlusion as a preventative measure to control anticipated intra-operative hemorrhage. Balloons were inserted in cath lab and shifted to operation theater for Cesarean Section. After the delivery of baby and during cord clamping, balloon was inflated and hysterectomy was carried out with minimal blood loss of 400ml. Keywords: balloon occlusion, cath lab, cesarean delivery, internal iliac artery, placenta accreta